Multicenter evaluation of ambulatory blood pressure in children with CAKUT: distinctive profiles in the cystic dysplasia subgroup - Yel, Sibel; Gunay, Neslihan; Yildirim, Pelin Abdal; Demir, Belde Kasap; Soyaltin, Eren; Kara, Aslihan; Poyrazoglu, Muammer Hakan (Springer, 2026)
Background Hypertension (HT) is an important risk factor in patients with congenital anomalies of the kidney and urinary tract (CAKUT), independent of the existing anomaly in childhood. This study aimed to investigate masked hypertension and/or blood pressure profiles in different subgroups with a normal glomerular filtration rate (GFR). Methods The study included participants from seven different pediatric nephrology centers in T & uuml;rkiye. Ambulatory blood pressure monitoring (ABPM) was performed on patients aged 5-18 years, diagnosed with CAKUT, with a GFR above 100 ml/min/m(2), and normal office blood pressure measurements. Validated Mobil-O-Graph or Spacelabs devices were used in all centers. Results In total, 118 healthy control data and 322 patients with CAKUT were evaluated, consisting of 73 (22.7%) with agenesis, 79 (24.5%) with cystic dysplasia, 92 (28.6%) with vesicoureteral reflux, 18 (5.6%) with UPJ (ureteropelvic junction) obstruction, and 60 (18.6%) with other conditions. In all CAKUT patients, daytime systolic blood pressure (SBP) and both day and nighttime diastolic blood pressure (DBP) loads were significantly higher compared to the healthy control group (p < 0.05). Nocturnal hypertension was identified in 58 (18%) of 322 children, whereas none of the control group presented hypertension. Children with cystic dysplasia had the highest nighttime hypertension proportions (22.7%) when compared to other subgroups. All data revealed higher total systolic-diastolic SDS and total mean SDS in the cystic dysplasia subgroup (p < 0.05). Conclusions The findings underscore the importance of blood pressure monitoring in the follow-up of patients with CAKUT, especially those with cystic dysplasia, even in the absence of GFR decline.
Keywords: Ambulatory blood pressure monitoring; CAKUT; Children; Masked hypertension; Cystic dysplasia